Analysis of Factors Influencing the Effectiveness of Local Government Asset Management in Local Government Agencies of Central Sulawesi Province - Ernita Wati; Muhammad Din; Mustamin (Pustaka Digital Indonesia, 2026)
The Audit Board (BPK) still finds several problems that are of concern to the Central Sulawesi Provincial Government, namely the internal control system and compliance. The purpose of this study is to test and analyze the influence of organizational commitment, regional management information system, human resource competence, human resource competence, government internal control system and the use of information technology on the effectiveness of regional asset management in the Central Sulawesi Provincial Government Apparatus Organization. The population of this study is 39 Regional Apparatus Organizations of Central Sulawesi Province. The samples taken using the purposive sampling method were Goods Administration Officials and User Goods Managers totaling 78 respondents. The type of research used in this study is a type of research with a quantitative approach. The results of this study show that the influence of organizational commitment, regional management information system, human resource competence, human resource competence, government internal control system and the use of information technology have a positive effect on the effectiveness of regional property management.